Analisis dan Penerapan Metode Tuning pada Basis Data Funding - Indrajani Indrajani (Bina Nusantara University, 2015)
The purpose of this research is to analyze, design, and implement tuning for the funding database, which include data mart processing that will be used in the formation of analytical reports. The research method used is literature study from a variety of journals, books, e-books, and articles on the internet. Fact findingtechniques are also done by analyzing, collecting, and examining the documents, interviews, and observations. Other the research methods are also used to analyze and design database such as SQL tuning, Partitioning, and Indexing. The results obtained from this research is an implementation tuning for the funding database, in which if it is implemented, it will improve performance significantly. The conclusion is by implementing tuning for the funding database, it can help the bank to improve the performance of database system and decrease time to produce analytical reports.